The response of denervated muscle to long-term stimulation (1985, revisited here in 2014) - Terje Lomo (PAGEPress Publications, 2014)
In 1985, at a meeting in Abano, I presented results showing that direct stimulation of skeletal muscles with appropriate stimulus patterns prevents the effects of denervation on non-junctional properties of muscle fibers. Hence, it appeared unnecessary to postulate that unknown nerve-derived trophic factors control such properties, as posited by the (anterograde) neurotrophic hypothesis. Here I discuss this conclusion in the light of what we know today, particularly with respect to the many lines of evidence that were then taken to support the trophic hypothesis, but which today have alternative interpretations consistent with control by evoked impulse activity. Despite much effort, no one has yet identified any nerve-derived factor consistent with the neurotrophic hypothesis. Reports favoring the existence of neurotrophic factors were numerous before 2000. Now they have essentially disappeared from the literature, including original research papers, textbooks and handbooks, suggesting that the hypothesis is no longer arguable. Thus, the results that I presented in our paper in 1985 seem to have held up rather well.